D-A type ambipolar electrochromic copolymers based on dithienopyrrole, 3, 4-propylenedioxythiophene and benzotriazole units with dual fading processes. (15th March 2023) - Gao, Zhujun; Kong, Lingqian; Ming, Shouli; Du, Hongmei; Zhang, Yan; Zhao, Jinsheng
Graphical abstract: Highlights: D-A type copolymers containing dithienopyrrole, 3, 4-propylenedioxythiophene and benzotriazole units were synthesized. The copolymers showed ambipolar electrochromic behaviors with dual fading processes. The copolymers exhibited desirable kinetic properties with low band gaps. Abstract: Three donor–acceptor (D-A) type electrochromic copolymers (PDPB-1, PDPB-2 and PDPB-3), employing dithieno[3, 2- b :2′, 3′- d ]pyrrole (DTP) and 3, 4-propylenedioxythiophene (ProDOT) units as donors as well as benzotriazole (BTz) units as acceptor, were synthesized by chemical polymerization with different feed molar ratios of the monomers. The three polymers possess double-doping ( p -type and n -type doping) electrochromic feature and relatively narrow optical band gaps (about 1.70 eV). Their solid films display slightly different blue colors in the neutral states including dark navy blue (PDPB-1), navy blue (PDPB-2 and PDPB-3), and all switch to light blue-gray after oxidation as well as to gray after reduction. The polymers also exhibit favorable kinetic properties, especially showing high optical contrasts and desired coloring efficiencies in the near-infrared (NIR) region. D-A type ambipolar electrochromic polymers with dual fading processes which display oxidized and reduced gray states are rarely reported in the literatures and such materials are obtained in this work by utilizing DTP units which are rarely used as building blocks for electrochromic copolymers.